Stepping into the Future Wisely: Shaping Savings Behavior In the Young Generation Through Financial Literacy Program: Shaping Savings Behavior In the Young Generation Through Financial Literacy Program - Tarigan, Ruth Abigail; Amba Dewi, Helmi; Wibowo, Agus (International Student Conference on Business, Education, Economics, Accounting, and Management (ISC-BEAM), 2024)
Saving is a way for individuals to reduce their consumption in order to have more money in the future. A poor attitude towards money management affects a person's ability to save, creates anxiety, and allows wasteful lifestyle habits to continue in everyday life. Encouraging thrifty behavior among teenagers is thought to reduce waste in consumption activities. This research found that sufficient financial knowledge can increase the saving behavior of the younger generation. Therefore, financial literacy programs should be improved and included in the curriculum at all levels of learning, with the aim of strengthening good attitudes in financial management, including saving, investing, understanding financial functions and services, and making wise financial decisions. In addition, schools and families must collaborate in providing practical and applicable financial education, as well as providing simulations or real exercises that can help teenagers understand and apply everyday financial concepts.